Il pastello nel Settecento europeo tra sapere scientifico e pratica artistica - Ottazzi, Alice (Venezia Arti, 2020)
The study of several French, British and Italian art treatises, articles, essays, and correspondences (mainly from the seventeenth and eighteenth centuries) leads to the analysis of the art of pastel as an example of the relation between scientific knowledge and artistic practice. The importance of following strictly specific recipes, as for the fixative methods as well, reveals not only the presence of a pragmatic purpose, but also aesthetic motives that could be connected to the development of the pastel practice in eighteenth-century Europe.